Analisis Standar Kerja Mahkamah Internasional Sebagai Mediator Dalam Penyelesaian Konflik Israel-Palestina (7 Oktober 2023) - Zubair, M Ferry; Firdaus, Muhammad Fadhil; Marsingga, Prilla (Faculty of Social and Political Sciences - Universitas Wahid Hasyim, 2024)
The crimes that Israel has committed against the Palestinian people have sparked outrage in the international community, especially South Africa, which has begun to drag Israel to the International Court of Justice on suspicion of genocide. The International Court plays a role as a third party in fulfilling the standard principles of work as a mediator to provide a resolution to the Israeli-Palestinian conflict. The research method used in this journal is a qualitative method with library study research methods. This research aims to increase readers' understanding regarding the working standards of the International Court of Justice which acts as a mediator in the Israeli-Palestinian conflict. It was decided to bring the Israeli occupation of Palestine to the level of the International Court of Justice after the UN General Assembly (UNGA) meeting on 30 December 2022. The majority of member states voted in favour of seeking a court opinion regarding the legal consequences of Israel's occupation of Palestine. To follow up on the UNGA, the International Court of Justice held a hearing session attended by 52 countries from 19 February 2024 to 26 February 2024. The International Court's function is to uphold international law and ensure that all parties involved in the conflict receive fair treatment. The decision resulting from the International Court of Justice trial is binding, meaning that the countries involved in the court must comply with what is stated in the decision. The interim ruling produced by the International Court of Justice emphasizes the importance of protecting human rights and compliance with the principles of international law. However, in reality, Israel is only implementing decisions such as opening humanitarian aid routes to Palestine.